Meristik, morphometric, FISH GROWTH PATTERNS AND PEARL Sepat (Trichogaster leeri). - Muslimatun '; Ridwan Manda Putra; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted in February-April 2013. Who caught 56 fish tail with a range of 113-185 mm in total length and weighing 28-82 grams of Canal Village Pomegranate and 32 tail with a total length range of 120 - 175mm and weighing 24-71 grams of Canal Village West Tangkerang. There are 13 characters that will be calculated meristik and 25 morphometric characters that will be measured in this study. The results of calculations of the Canal Village meristik Pomegranates: D.VI-V. 9-10-40, p.9-16, A.VI-XI.30-40, C.16-21 and the Village of Canal West Tangkerang XII.9-DV-10, p.8-15, AX-XIII .31-38, C.10-19. Average number of scales on the fish scales Sepat siam front dorsal fin 23-28, 32-41 scales in the lateral linea, linea scales above lateral 11-14, scales below the linea lateralis 50-63, 50-66 scales around the body and 30-38 scales on the tail shaft. There is a pattern 4kelompok proportion Sepat siam fish morphometric characters of Channel 4 Pomegranate Village of Canal Village West Tangkerang pattern groups the proportion of fish Sepat siam morphometric characters of Canal Village Pomegranate Sepat siam fish growth patterns in Pomegranate Channel and Canal West Tangkerang the negative allometric (Canal Village Tangkerang West, male and female b = 0.107 b = 0.151) and at Canal Village Pomegranate (male, female b = 0.096 and b = 0.061). Sepat siam fish traits can be seen from the high dorsal fin, caudal fin height to distinguish male fish and beitina Sepat siam.Key words: Trichogaster pectoralis, Pomegranate Canal Village, Canal Village West Tangkerang,morphometric characters, character meristik